A dose response relation for noise induced hypertension. Issue 3 (March 1991) - Zhao, Y M; Zhang, S Z; Selvin, S; Spear, R C
Abstract : The effect of industrial noise on the prevalence of hypertension was studied in a group of 1101 female workers in a textile mill in Beijing in 1985. Essentially the entire group had worked in specific workshops in this mill for all their working lives and all had worked for at least five years. The noise levels within the plant were assessed and appear to have been constant since 1954 resulting in well defined noise exposures for these workers. A cross sectional design was used in which blood pressures were determined and questionnaires administered to the workers over a two month period. As well as demographic information, data were gathered on personal and family history of hypertension, current use of prescription drugs, alcohol, tobacco, and salt in the diet. Logistic regression indicated that exposure to noise is a significant determinant of prevalence of hypertension, but third in order of importance behind family history of hypertension and use of salt. Each of the predictor variables exerted an independent influence on risk of hypertension. Cumulative exposure to noise was not an important dose related variable suggesting that, for those susceptible to the effect, hypertension was manifested within the first five years of exposure.